Issues of Improving the Financial State of Management Service Companies - Mamanazarov Oybek Shomurodovich; Karimova Aziza Azamiddin kizi (Scientific Trends, 2025)
This article discusses the issues of improving the financial condition of management service companies in Uzbekistan.
Keywords: Management service companies (MSC), financial position, balance sheet analysis, income statement (profit and loss statement) analysis, cash flow statement analysis, financial ratio analysis.